STRATEGI GURU DALAM MENGINTEGRASIKAN DEEP LEARNING UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS - Wijayanti, Isnaeni; Diah Sunarsih; Laelia Nurpratiwiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students’ critical thinking skills in mathematics learning need to be developed through strategies that support deep learning. This study aimed to describe teachers’ strategies in integrating deep learning to develop fourth-grade students’ critical thinking skills at SD Negeri Bulakparen 01 in mathematics learning. This research employed a qualitative approach with a descriptive phenomenological design involving one teacher and six fourth-grade students as research informants. Data were collected through interviews, observation, and documentation. The data were analyzed using the Miles and Huberman model. The findings revealed that teachers integrated deep learning through meaningful learning, mindful learning, and joyful learning. Meaningful learning was implemented by relating mathematics materials to students’ daily lives. Mindful learning was applied through higher-order questioning and problem-solving activities, while joyful learning was carried out through simulations and enjoyable learning activities. These strategies helped students become more active, understand concepts meaningfully, and develop critical thinking skills in mathematics learning.